Financial reporting quality of financial institutions: Literature review - Ahmed Mahdi Sahi; Alaa Mahdi Sahi; Alhamzah F. Abbas; Saleh F. A. Khatib (Cogent Business & Management, 2022)
The objective of this study is to examine and synthesize the existing literature on financial disclosure by financial institutions. It presents a systematic literature review of 204 studies on this topic published from 1990 to 2022. The studies were retrieved from Scopus database. In addition, this review highlights the gaps in current literature including contradictory results, explores the potential data sources for empirical researchers, and offers guidance for investigating prospective areas for future studies. The study found monitoring attributes to be the key determinants of financial reporting quality. Yet, the existing literature concentrated on internal/external auditing and audit committee characteristics whilst giving limited attention to the functions of other monitoring mechanisms, i.e., board of directors. Furthermore, there is no clear evidence that efficient financial disclosure could boost the performance and evaluation of firms as well as whether these consequences are influenced by differences in the institutional and protection environment between markets. The contribution of this study resides in the application of systematic literature review to a burgeoning study topic, enabling an examination of the state-of-the-art financial reporting in financial institutions, an area that has received little attention in the literature. Based on the content investigation of the literature, future paths and implications are also presented.
Keywords: 650; financial institutions; banks; accounting disclosure; online financial reporting